Apparently healthy urinary bacteriology in children - Burstein de Herrera, S. (1968)
Bacteriological study of urine of 350 apparently healthy children who were divided into groups according to the various stages of childhood ago. In each study urine sediment , gram staining and the qualitative and quantitative culture was performed. The study revealed three maximum sediment leukocytes per microscopic field in 12.3 % of things and 1-2 erythrocytes per field in 6.28 %. No clear cylinders or inflammatory cells were observed . QRAM by coloring germs no sediment or total urine were detected. The qualitative culture was positive in 58% of cases have been isolated most often staphylococcus , coli and Klebsiella . However, quantitative culture revealed that the germ count did not exceed the threshold of 5 x 103, and that most cases ( 71 % ) had less than 1,000 bacteria per ml. , Or that were merely contaminants. This shows the importance of quantitative culture to differentiate true bacteriuria from contamination in the urine of children, in which there is great difficulty in obtaining a urine sample in good condition.